THE SUPPORT AND MONITORING PROGRAM FOR ADOLESCENTES AND YOUNG PEOPLE OF THE PROGRAMA OF EGRESSES IN THE CITY OF SALVADOR - de Jesus, Evandro Luís Santos; de Fátima Pessôa Lepikson, Maria (Seven Editora, 2025)
This article seeks to briefly address the factual and legal situation surrounding the Support and Monitoring Program for adolescents and young people released from prison in the Socio-Educational Assistance Communities (CASE) in the city of Salvador. This essay stems from studies on the topic and aims to reflect on its undeniable relevance in the Brazilian justice system. This exploratory research uses both quantitative and qualitative approaches, aiming to understand the social phenomena studied, particularly through the analysis of data contained in documents from the Public Prosecutor’s Office of the State of Bahia (4th Public Prosecutor’s Office for Children and Youth, 2nd Public Prosecutor’s Office of the Capital). It also highlighted the weakness of the work that should be carried out within the support network, at all stages of contact with adolescents and young people entering the criminal world, whether before, during, or after their release, from the perspective of institutional incompleteness. It was found that other alternatives exist to guarantee the rights of adolescents and young people both during the fulfillment of socio-educational measures involving deprivation of liberty and after their release, which can be implemented to create possibilities for them to have new paths. DOI: https://doi.org/10.56238/sevened2025.029-056